Ion track etching revisited. V. Etching of aged pristine and swift heavy ion-irradiated polyimide foils after treatment in hot ambient. Issue 1 (1st February 2021) - Fink, D.; Vacik, J.; Hnatowicz, V.; Kiv, A.
Abstract : In the previous papers of this series, the result of etching of fresh swift heavy ion (SHI)-irradiated polyethylene terephthalate (PET) foils after thermal annealing in various environments was studied to determine the extent to which thermal annealing is able not only to simulate aging of pristine polymer foils, but also SHI-irradiated foils. The etching results of these foils (obtained using breakthrough times of the etchant across the PET foils that were pre-annealed at different temperatures for constant times) did not always follow the predicted Arrhenius behavior, but showed dip-like deviations that were tentatively attributed to both SHI radiation and ambient effects to the glass transition temperature. To determine whether deviations from the simple Arrhenius behavior also occur for other irradiated polymers, we examined the effect of thermal annealing at different temperatures T of aged SHI-irradiated Kapton foils via the etchant breakthrough times across the SHI tracks. Interestingly, there appeared unexpected wide dip-like deviations from straight Arrhenius plots. Comparison of this curve with corresponding ones of aged non-irradiated Kapton foils, by determining the etchant breakthrough times across the foils, enabled us to assign the obtained high-temperature Arrhenius branch (for T  > 80°C) to heal both aged and irradiated polymer foils from aging and/or radiation defects. In contrast, the pristine and irradiated aged samples annealed at lower temperatures follow completely different trends. As in the previous article on PET, we tend to assign the dip-like deviation of the SHI-irradiated Kapton again to the glass transition temperature of this highly radiation-damaged material.